Pengembangan Daya Tarik Wisata Heritage Museum Situs Kota Cina Kelurahan Paya Pasir Kecamatan Medan Marelan Kota Medan - Joel Parluhutan Tamba (Politeknik Pariwisata Medan, 2023)
This research was conducted to get an overview and information about the role of managers in developing the tourist attractions of the Cinna Cotta Site Museum and its impact on the economy of the surrounding community. In writing this research, the author conducted research at the Cinna Cotta Site Museum located on Jl. Kota Cina Kelurahan Paya Pasir, Medan Marelan District, Medan City, North Sumatra 20254. The research method carried out by the author is a qualitative research method. The approach and type of research are descriptive, namely through direct observation, interviews, documentation, and literature studies related to relevant theories in analyzing existing problems. The subject of this study was the manager of the Cinna Cotta Site Museum and the community / merchants around the museum. Based on the results of research obtained at the Cinna Cotta Site Museum, it has a very potential tourist attraction to be developed. The role of the manager greatly influences the development of the museum but the development carried out has not been optimal and has not been in accordance with the plan. But the impact felt by the community with the existence of the Cinna Cotta Site Museum is quite good, because with the existence of the Cinna Cotta Site Museum, people's knowledge and income has increased. Keywords: Attractions, Heritage Tourism, Development, Managers, Communities.